Compressive Properties of Carbon Fibre Reinforced Plastic (CFRP) at Low Strain Rate - Ahmad, Roslan; Mohd Ripin, Zaidi; Pasricha, M. S. (Universiti Putra Malaysia Press, 2001)
An experimental programme was carried out for testing and characterising the mechanical properties of carbon fibre reinforced plastic (CFRP) at low strain rates ranging from 10-' to 10 Is. Transverse compressive properties were obtained by carrying a series of quasi-static and dynamic tests on filament wound CFRP tubes with winding angle of ± 90° (the angle is relative to the tube axis). The quasi-static test were carried out using an Instron and RDP machines whereas dynamic tests on drop hammer rig. Axial and hoop strains were measured by foil strain gauges bonded to the specimen inside and outside surfaces. Load-displacement, load time and strain-time signals recorded during relevant tests are used to produce stresss train curves. The transverse compressive strength and ultimate failure strain increases with increasing strain rate. The modulus and Poisson's ratio are independent of strain rate. The stress strain curves at different strain rates exhibit a degree of non-linearity. No rate effect is observed on the mode of failure.